Pengaruh Penggunaan Media Komik Dalam Meningkatkan Minat Dan Hasil Belajar Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas Ii Di SDN 5 Kasongan Lama Kecamatan Katingan Hilir Kabupaten Katingan Tahun Ajaran 2024/2025 - Kika, Kika; Bungai, Joni; Abdul Rahman Azahari (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
This research is motivated by the problems that occur at SDN 5 Kasongan Lama, namely the scores obtained by students are still far from the set KKM. Based on observations, it is also known that one of the causes of the low learning outcomes of Indonesian Language is the lack of interest of students in learning Indonesian Language subjects and the lack of use of media in classroom learning. The purpose of this study is to increase the interest and learning outcomes of grade II students in Indonesian Language subjects at SDN 5 Kasongan Lama by using comic media. This research is included in the type of quasi-experimental research carried out in two classes. The experimental class consists of eight meetings. The control class consisted of six meetings. The subjects of this study were grade II students of SD Negeri 5 Kasongan Lama in the Indonesian Language subject in the odd semester of the 2024/2025 Academic Year, totaling 30 students from the experimental class and 29 students from the control class. Data collection techniques used pretest, posttest, questionnaires, and documentation. The data analysis technique used in this study was quantitative data and Data analysis was calculated using the Chi-square formula, Fisher's formula and T-test formula. The results of the study showed that the average pretest value of student learning outcomes in the experimental class was 60.5 and the average posttest value of student learning outcomes in the experimental class after participating in learning using comic media increased by 78.83. Based on these data, it shows that there is an influence of the posttest of 18.33. and the average value of p7 student learning interest in the experimental class was 29.23 and the average p8 student learning interest in the experimental class in both meetings used comic media in the learning process, both meeting 7 and meeting 8 and experienced an increase of 2.9 or 7.3%. Furthermore, it can be concluded that there is a positive influence that comic media can increase the interest and learning outcomes of class II students of SDN 5 Kasongan Lama in the 2024/2025 academic year